Associations of First Void Urine Samples with Bacterial Vaginosis - Shabnum Jaffri, Shahzad Bashir Momana, Sajida Imran, Mohammed Alorini, Nosheena Shabir, Muhammad Ahmad Albajuri (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study was to investigate whether BV can be diagnosed from first-void urine (FVU). Study Design: Cross-sectional/case control study Place and Duration: Conducted at Hameed Latif Hospital Lahore, during from Sep, 2021 to Feb, 2022. Methods: There were 100 women had ages 20-65 years was presented in this study. Once informed written consent was obtained, participants’ detailed demographic information was recorded. First void urine was collected from all women. According to Nugent’s criteria, BV was indeed diagnosed. All of the qPCRs performed on the FVU and vaginal swabs for the selected vaginal bacteria (Atopobium vaginae, Prevotella spp., Gardnerella vaginalis, bacterial vaginosis-associated bacterium 2, Eggerthella-like bacterium, "Leptotrichia amnionii," Megasphaera type 1) had an area under the receiver operating characteristic (ROC) curve of >85%, All data was examined using SPSS 24.0. Results: In current study, mean age of the women was 28.11±15.68 years and had mean BMI 24.9±7.49 kg/m2. Majority of the females were nulliparous 67 (67%). Most of the females had no genital hair remove among 60 (60%). Among 100 females, 49 (49%) females had bacterial vaginosis, 40 (40%) had normal vaginal flora and 11 (11%) had intermediate flora. Nugent scoring was used to determine the sensitivity and specificity of seven assays for BV-associated bacteria in urine (A. vaginae, Prevotella spp., G. vaginalis, BVAB 2, Eggerthella-like bacterium, L. amnionii, and Megasphaera type 1). By qualitative detection, the assays were 80%-100% sensitive but only 8%-80% specific (presence or absence). The area under the curve (AUC) was > or = 91% for all seven bacterial species, indicating high diagnostic accuracy. Conclusion: Our research of ROC curves led us to the conclusion that FVU can be used to accurately diagnose BV. Combining qPCR findings for two bacteria, like Megasphaera type 1 and Prevotella spp., can improve sensitivity or specificity, respectively. Keywords: First Void Urine, BV, PCR, Nugnet scoring. 7-Assays